Single centre concept of 'cold site' elective surgery during the peak of COVID-19 pandemic : A cohort study. (November 2020) - Iqbal, Muhammad Rafaih; Dhahri, Adeel Abbas; Darwish, Nourelhuda Mohammed Mustafa; Vijay, Vardhini
Abstract: Objective: The COVID-19 pandemic caused a major strain on healthcare systems across the globe. As these systems got overwhelmed with the emergency care of the infected patients, widespread cancellations of elective surgery occurred. Our hospital utilised local private hospital as a dedicated cold site (CS) for urgent elective surgery during the peak of the COVID-19 pandemic. We aim to analyse the outcomes at this dedicated cold site. Method: A retrospective review of a prospectively maintained database of all the cases operated at the CS during a 2-month period (30 March 2020 to 29 May 2020) was carried out. The primary outcome was 30-day COVID-19 related mortality. The secondary outcomes were 30-day non-COVID-19 related mortality, complications, readmission and development of COVID-19 symptoms. Results: A total of 153 patients were operated at the CS over the study period with a median age of 57 years (Interquartile range, IQR 47–70). 62% were females and 82% had a Body Mass Index (BMI) less than 30. 73% of the operations were performed for cancer. 59% of the surgeries were graded as intermediate and 26% as major or complex. There was no mortality at 30 days from COVID-19 or non COVID-19 causes. There was only 1 (0.65%) readmission. 7 patients (4.57%) developed complications. 1 (0.65%) patient was diagnosed with COVID-19 in the postoperative period while 3 had COVID-19 symptoms but were tested negative. Conclusion: Urgent elective surgery is safe and feasible during the COVID-19 pandemic if a dedicated cold site is available. Highlights: This study reports findings of a dedicated cold site elective surgery during the peak of COVID-19 pandemic. There was no COVID-19 or non-COVID-19 related 30-day mortality. There was only one (0.65%) 30-day readmission and one patient (0.65%) had COVID-19 in the post-operative period. Dedicated cold site with multi model approach using careful patient selection and appropriate infection control measures including personal protective equipment is safe and feasible.